Outcome of infantile nephropathic cystinosis depends on early intervention, not genotype: A multicenter sibling cohort study. Issue 1 (6th October 2022) - Veys, Koenraad; Zadora, Ward; Hohenfellner, Katharina; Bockenhauer, Detlef; Janssen, Mirian C. H.; Niaudet, Patrick; Servais, Aude; Topaloglu, Rezan; Besouw, Martine; Novo, Robert; Haffner, Dieter; Kanzelmeyer, Nele; et al.
Abstract: Infantile nephropathic cystinosis (INC) is an inheritable lysosomal storage disorder characterized by lysosomal cystine accumulation, progressive kidney disease, and multiple extrarenal complications (ERCs). Cysteamine postpones the onset of end‐stage kidney disease (ESKD) and reduces the incidence of ERCs; however, cysteamine is generally initiated upon establishment of the renal Fanconi syndrome (FS) and partial loss of kidney function, whereas data on long‐term effects of cysteamine administered from neonatal age are lacking. An international multicenter retrospective cohort study of siblings with INC was set up to investigate the outcome in relation to age at initiation of cysteamine versus CTNS genotype, with attention to patients treated with cysteamine from neonatal age. None of the siblings treated from neonatal age ( n  = 9; age 10 ± 6 years) had reached ESKD, while 22% of their index counterparts ( n  = 9; age 14 ± 5 years) had commenced renal replacement therapy. Siblings treated with cysteamine from the onset of symptoms at a younger age compared with their index counterparts, reached ESKD at a significant older age (13 ± 3 vs. 10 ± 3 years, p  = 0.002). In contrast, no significant difference in ERCs was observed between sibling and index patients, independently from the age at initiation of cysteamine. The CTNS genotype had no impact on the overall outcome in this cohort. In INC, presymptomatic treatment with cysteamine results in a better renal outcome in comparison to treatment initiated from the onset of symptoms. This justifies including cystinosis into newborn screening programs. Synopsis: In infantile nephropathic cystinosis, presymptomatic treatment with cysteamine improves the renal outcome which justifies the inclusion of cystinosis into newborn screening programs.